If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(x+7)-(3x-7)=9
We move all terms to the left:
8(x+7)-(3x-7)-(9)=0
We multiply parentheses
8x-(3x-7)+56-9=0
We get rid of parentheses
8x-3x+7+56-9=0
We add all the numbers together, and all the variables
5x+54=0
We move all terms containing x to the left, all other terms to the right
5x=-54
x=-54/5
x=-10+4/5
| (y-7)-(y+9)=4y | | (1+x)^5=1.16 | | 7(x-3)=29 | | 0.5x+3=66.66x+1 | | 6a-9=6a+7 | | 38+90+(8m+4)=180 | | 7y+4=32-10y+3y | | -6(x+5)+3=-2(x+4)4x | | −2(4x−1)=−8x−1 | | 7a-14=5a+8 | | 2x+10×130=180 | | 2n-9= | | 75+4x=42+7x | | 9x-4.5= | | 2(4x−1)=−8x−2 | | 400×5=2x | | 15x+2=9x= | | 180=16x=8(4x-8) | | -120+40w=1200 | | 6n+4=10n | | 132-2(2b-3+1=11 | | 2.3w=9.2+1.9w | | -3=5x+22 | | 10y=-17=23 | | 120+19x+6=180 | | 100+x+111=180 | | 0.75x-6=2 | | 5x+16=91* | | -5•12d+64=356 | | 4x-1/2=4x+3 | | 4=1+n/4 | | -2x-2.5+1.8=3.2 |